METTL3 Promotes the Progression of Gastric Cancer via Targeting the MYC Pathway - Yang, Dong-Dong; Chen, Zhan-Hong; Yu, Kai; Lu, Jia-Huan; Wu, Qi-Nian; Wang, Yun; Ju, Huai-Qiang; Xu, Rui-Hua; Liu, Ze-Xian; Zeng, Zhao-Lei (Frontiers in Oncology, 2020)
m6A methyltransferase-like 3 (METTL3), a major component of the N6-methyladenosine (m6A) methyltransferase complex, has been suggested to function as an oncogene in several cancers. However, its biological mechanism and the involved pathways in gastric cancer (GC) remain unknown. Here, we reported that frequent upregulation of METTL3 is responsible for the aberrant m6A levels in gastric carcinoma. On the other hand, a high level of METTL3 is significantly associated with several clinicopathological features and poor survival in patients with GC. The knockdown of METTL3 effectively inhibited cell proliferation and migration and invasion capacity. Moreover, overexpression of METTL3 considerably augmented its oncogenic function. Integrated RNA-seq and m6A-seq analysis first indicated that several component molecules (e.g., MCM5, MCM6, et al.) of MYC target genes were mediated by METTL3 via altered m6A modification. Our work uncovers the oncogenic roles of METTL3 in gastric carcinoma and suggests a critical mechanism of GC progression.